Woodrow Wilson - Cude, Michael, author.
1 online resource.
Keywords: "This volume contributes to the Routledge Seminar Studies history series by providing a concise, narrative overview of the ideas and foreign policy of Woodrow Wilson. It focuses on Wilson's response to the First World War and his efforts to formulate a new international system, while also outlining Wilson's policies toward different parts of the world. The book shows how Wilson shaped the direction of the 20th century in areas such as global governance, nationalism, decolonization, and international relations theory. In doing so, the book introduces the reader to the many debates over Wilsonian foreign policy. With a target audience of college undergraduates and non-experts, readers will gain a better understanding of Wilson's vision for the world, his administration's approaches to foreign policy, particularly during the First World War, and the global impact of his program"--